Jual Beli Online Dalam Perspektif Hukum Islam - Tarikha Khainursyah Siregar; Khairunnisa Tanjung; Jihan Safa Batubara; Bunga Natasyah (Albayan Journal of Islam and Muslim Societies, 2024)
The development of information technology has driven changes in economic activities, including in the practice of buying and selling which can now be done online. Online buying and selling provides convenience for the community, but also raises concerns about its validity and permissibility in the eyes of Islam. This study aims to examine online buying and selling based on the perspective of Islamic law, with a qualitative approach through literature study. The results of the study indicate that online buying and selling can be categorized as valid and permissive as long as it meets the pillars and conditions of the contract that have been set in Islamic law, such as clarity of the object of the transaction, agreement between both parties, and does not contain elements of gharar, fraud, or usury. This study confirms that the basic principles of muamalah in Islam provide room for transaction innovation as long as it is based on the values ​​of justice and transparency. Therefore, online buying and selling is permitted as long as it does not conflict with the principles of Islamic law.